EL CINE ROMÁNTICO HOLLYWOODIENSE DE LA PRIMERA DÉCADA DEL S. XXI: ANÁLISIS DESDE LA PERSPECTIVA DE GÉNERO - Dra. Beatriz MORALES ROMO,Dra. Noelia MORALES ROMO (Fonseca, Journal of Communication, 2023)
This work studies the romantic cinema to reflect, on the one hand, the characteristics and evolution of this genre through the great Hollywood productions and, on the other, the implications that the reflected image can have on younger viewers, regarding the values and ideals on gender construction that they transmit. The aim is to determine whether there is a public profile to which these romantic films are targeted, to know the images offered of men and women, as well as their relationships and which model or models of relationships are transferred from the big screen.